Optimized synthesis/design of the carbonator side for direct integration of thermochemical energy storage in small size Concentrated Solar Power. (December 2019) - Tesio, U.; Guelpa, E.; Ortiz, C.; Chacartegui, R.; Verda, V.
Highlights: High-temperature thermochemical energy storage for Concentrated Solar Power. Discharge phase of the Calcium Looping direct integration in small scale plant. Optimization performed both on heat exchange and process components. Multi-objective analysis for tradeoff between efficiency and layout complexity/size. Solution for the violation of heat exchanger network design constraints. Abstract: Two of the most attractive characteristics of Concentrated Solar Power are the high-quality heat exploitable and its capacity for thermal energy storage, which enhance the energy dispatchability in comparison with other renewable sources such as photovoltaics or wind. Consistent efforts are therefore direct to the research of suitable thermodynamic cycles and energy storage systems with low thermal losses and high operating temperatures. However, in the most developed technologies, based on sensible and latent heat storage, high thermal losses are the direct consequence of high operating temperatures. As alternative, Thermochemical Energy Storage systems are gaining attention in the last years. The present work investigates the adoption of a novel Calcium-Looping system for Thermochemical Energy Storage, focusing on the integration on carbonator side. This key integration is directly linked to the energy delivery from the energy storage system and therefore power generation capacity of the plant. An optimization of the carbonator side plant is performed for a direct integration layout, where carbon dioxide from the carbonator evolves through the power block. This analysis aims to maximize the system efficiency acting both on the process components operation and on the thermal transfer between the involved streams. The optimization relies on a novel method based on a genetic algorithm. The pinch analysis is adopted for this study and proper constraints are provided to obtain a configuration exploiting only the renewable energy source. A multi-objective optimization is performed to find out the heat exchanger network topology changes that occur for different operating conditions and derived from this analysis suggestion for systems integration are provided.